THE DISCOURSE OF WOMEN'S PIETY AND GENDER BIAS CONSTRUCTION ON MUSLIMAH WEBSITES IN INDONESIA - Achmad Rifai (al-Balagh : Jurnal Dakwah dan Komunikasi, 2021)
The presence of the internet as a marker of the emergence of new media cannot be denied, raising the concept of digital religion as an important element in the presentation of religion at the level of the digital world landscape. In Indonesia, the encounter of Muslim women with the internet has presented religious narratives within the scope of the online world, not least in terms of discourse on gender issues. Using the netnographic method and supported by content analysis, this paper attempts to research and analyze two websites, specifically muslimahnews.com and muslimah.or.id. The findings indicate that the two websites, which contain discourses on women's piety and gender bias, demonstrate that gender inequality on the internet is not directly caused by a lack of women participation but rather by a strong interpretation of gender-biased Islamic ideology in the real world, which is reflected in the virtual world. In other words, the existence of gender bias in Muslim women's websites in Indonesia is a matter of using technology. It is also caused by the construction of gender-biased religious ideology, which previously existed in the offline landscape.